Polymers encapsulated aspirin loaded silver oxide nanoparticles: synthesis, characterization and its bio-applications - Ahmad, Shabir; Rashid, Hira; Jalil, Qudisa; Munir, Sidra; Barkatullah,; Khan, Sulaiman; Ullah, Riaz; Shahat, Abdelaaty A.; M. Mahmood, Hafiz; A-Mishari, Almoqbil A. Naser AbdullahAlmoqbil A. Naser Abdullah; Bari, Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2019)
Simple, facile and cost effective approach is used for the synthesis of Aspirin based silver oxide nano-particles (SONPs) by chemical wet method. The synthesized SONPs were loaded with Aspirin to form Asp-SONPs, which was confirmed with the help of UV spectroscopy. Characterization was done using spectroscopy techniques FTIR, SEM, TEM and XRD. Antimicrobial assay of Asp-SONPs were carried out against six bacterial strains (E. coli, Protues, Vibrio, Citrobacter, Enterobacter, S. aureus) and fungal strains (Curvularia, Alternaria, Rhizopus, Aspergillus, Helmithosporium, Paecilomyces) by well diffusion method which confirmed its potential application as an antimicrobial agent. Asp-SONPs-PVA also displayed highest insecticidal activity against both tested insects (Tribolium casterium and Callosobruchus chinensis) having LC50 value of 15.917, and 37.6365 and highest percent mortality at 1000 ppm was 67%, and 73%, respectively. PVA coated SONPs displayed encouraging phytotoxicity when exposed to allopathic, where Asp-SONPs coated PVA give excellent anthelmintic activity by killing or paralyzing all the species (earthworm) at 1000 ppm.